Effect of Canavanine on Murine Retrovirus Polypeptide Formation - Murphy, Edwin C. (1980)
Canavanine is an arginine analog which is widely used to inhibit proteolytic processing of viral polyproteins. Certain results obtained with canavanine have suggested that it may have other effects. Therefore, we examined the effects of canavanine on the cell-free synthesis of murine retrovirus proteins. It was found that the electrophoretic mobility of the major gag-related cell-free product of both Rauscher murine leukemia virus (R-MuLV) and Moloney murine sarcoma virus 124 (Mo-MuSV-124) RNA was dependent on the concentration of canavanine used during translation. As the canavanine concentration was increased up to 4 mM, the apparent size of the major gag-related polypeptide also increased from 65,000 (R-MuLV RNA) or 63,000 (Mo-MuSV-124 RNA) to approximately 80,000 daltons. Additional increases in the canavanine concentration up to 12 mM did not increase the size of the gag gene product beyond 80,000 daltons. This change in electrophoretic mobility appeared to be due to a substitution of canavanine for arginine residues in the polypeptides, not to a change in their actual size. If amber suppressor tRNA and canavanine were used together during translation of Mo-MuSV-124 RNA and Mo-MuLV RNA, the results were also in agreement with this proposal. Translation experiments done with ovalbumin mRNA and mengovirus 35S RNA indicated that canavanine incorporation caused a shift in the electrophoretic mobility of ovalbumin from 43,000 to 45,000 daltons and caused the appearance of two slightly larger polypeptides in the 155,000- and 115,000- dalton regions of the mengovirus RNA cell-free product.